The reference librarian is now online understanding librarians' perceptions of quality chat reference using critical incident technique - Eclevia, Marian Ramos (2012)
This article attempts to understand the librarians' perceptions of quality chat reference services of selected academic libraries in the Philippines. It aims to investigate the perceptions of librarians in terms of (1) chat reference definition; (2) similarities and differences of reference interview in chat reference and traditional reference; (3) advantages and disadvantages of chat reference and in-person reference; and, (4) successful and less successful experience in chat reference. Using the Critical Incident Technique (CIT), a survey of 20 library staff who perform chat reference services in UP Diliman and UP Los Banos was conducted. A total of 76 critical incidents were analyzed using MAXqda, where 61.84% were positive incidents. The success of chat interactions was dependent on librarians' knowledge of information resources and, a fast and stable Internet connection.